KESIAPAN PEMBELAJARAN DARING TIDAK BERHUBUNGAN DENGAN MOTIVASI BELAJAR DI MASA PANDEMI COVID-19 - Muflih, Raihan; Samara, Diana (Fakultas Kedokteran Universitas Trisakti, 2022)
INTRODUCTION In the midst of the chaos caused by the COVID-19 pandemic, Indonesia can continue its formal education system with an online learning system. However, the online learning system as an alternative to the classroom teaching system was dismissed, considering the risk of contracting COVID-19 to students and teachers. This research aims to determine the correlation between online learning readiness and high school students learning motivation. METHODS This study was a cross-sectional study with analytical observations on high school students who were studying online with the same subject and the same teacher. 62 male and female respondents aged 15-17 were collected by consecutive random sampling. The research tools were the Online Learning Readiness Assessment (OLRA), and Situational Motivational Scale (SIMS) questionnaires filled out by the respondents. SIMS was measured using the Self-Determined Index (SDI) to determine intrinsic and extrinsic motivation categories. The results were then tested using the Pearson correlation test. RESULTS 54.8% of students were “not ready” for online learning, 30.6% were “almost prepared”, 12.9% were “not suited” for online learning, and 1.6% were “ready” for online learning. There was no statistically significant difference between extrinsically motivated students (53.2%) and intrinsically motivated (46.8%). There was no correlation between online learning readiness and motivation of the students (r=-0.051, p=0.692). CONCLUSION More students are not ready for online learning. However, it is not correlated between online readiness and students’ learning motivation. KEYWORDS: Online learning, Learning Motivation, High School, COVID-19 Pandemic